Hepatorenal syndrome in decompensated portal hypertension - M.I. Tutchenko; M.S. Besedinskyi; S.A. Aslanian; I.V. Kluzko; D.V. Rudyk; S.L. Chub (Medičnì Perspektivi)
Hepatorenal syndrome is the development of kidney failure in patients with decompensated chronic diseases with portal hypertension. This study aimed to search for  optimal methods of early diagnostics, therapeutic approaches and establishment of lethality causes in hepatorenal syndrome. The research presents the outcomes of treatment of 192 patients diagnosed with hepatorenal syndrome and undergoing inpatient care at the Municipal non-profit enterprise “Kyiv City Clinical Emergency Hospital” and the Clinic of the Department of Surgery of the Dental Faculty of the Bogomolets National Medical University between 2018 and 2023. Renal dysfunction and increased creatinine were detected in 192 (43.9%) out of 437 patients with decompensated portal hypertension, who were subsequently divided into two groups based on the degree of decompensation. The first group, comprising 57 (29.7%) patients, fell into class B according to the Child-Pugh scale and had <30 points according to the MELD scale. The second group consisted of 135 (70.3%) patients classified as class C and ≥30 points according to the MELD scale. In the treatment of hepatorenal syndrome, as well as in order to ensure an euvolemic state and prevent circulatory dysfunction, after therapeutic paracentesis, an infusion of 20% albumin solution at the rate of 6-8 g/l of evacuated ascites was used. The appointment of terlipsin in patients with portal hypertension complicated by bleeding in the presence of hepatorenal syndrome had a double effect in the form of a constrictor effect aimed both at stopping bleeding and at changing the splanchnic blood flow, which contributes to the improvement of kidney function. Stopping bleeding, eliminating the infectious factor in ascitic fluid, reducing intra-abdominal pressure, correcting biochemical parameters, and optimizing intra-abdominal blood flow were components of the treatment of hepatorenal syndrome. Depending on the combination of the number and severity of complications of portal hypertension, the number of unsatisfactory treatment results also increased. The total mortality in the development of hepatorenal syndrome was 80.2%. The primary criterion for diagnosing hepatorenal syndrome is the control of diuresis and its daily decline, coupled with an increase in creatinine levels exceeding 30 mmol/l within 48 hours.Varicose bleeding, severe ascites accompanied by intra-abdominal hypertension, and spontaneous bacterial peritonitis serve both as triggering factors for hepatorenal syndrome development and increase mortality rates.